2021
DOI: 10.3892/etm.2021.10451
|View full text |Cite
|
Sign up to set email alerts
|

Aging reduces kisspeptin receptor (GPR54) expression levels in the hypothalamus and extra‑hypothalamic brain regions

Abstract: Aging leads to the diminished pulsatile secretion of hypothalamic gonadotropin-releasing hormone (GnRH). Kisspeptin (Kp), the upstream regulator of the hypothalamic-pituitary-gonadal (HPG) axis, regulates GnRH synthesis and release through its cognate receptor, G-protein coupled receptor 54 (GPR54). In turn, GnRH regulates GPR54 expression. GnRH administration into the third ventricle has been shown to induce neurogenesis in different brain regions in old age. However, aging-associated changes in hypothalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
5
0
6
Order By: Relevance
“…KISS was negatively correlated with age, BMI, CRP, and serum leptin level among participants with CF. Serum KISS levels of healthy women were found to be significantly and negatively correlated with age (R = − 0.458) in the study by Erel et al 43 Declined levels of KISS and its receptor in different brain regions with age were also observed in animal studies 44 . Sitticharoon et al revealed that serum KISS was positively correlated with body weight, BMI, and serum leptin in male subjects 31 .…”
Section: Discussionmentioning
confidence: 84%
“…KISS was negatively correlated with age, BMI, CRP, and serum leptin level among participants with CF. Serum KISS levels of healthy women were found to be significantly and negatively correlated with age (R = − 0.458) in the study by Erel et al 43 Declined levels of KISS and its receptor in different brain regions with age were also observed in animal studies 44 . Sitticharoon et al revealed that serum KISS was positively correlated with body weight, BMI, and serum leptin in male subjects 31 .…”
Section: Discussionmentioning
confidence: 84%
“…В исследовании на крысах разного возраста было показано, что экспрессия GPR54 (аналог KISS1R у крыс) и КП в гипоталамусе значительно снижается при старении. Авторы предполагают, что снижение уровня КП и его рецептора GPR54 в гипоталамусе может быть ответственным за снижение уровня ГнРГ, наблюдаемое в пожилом возрасте [30]. Кроме того, показано, что КП выполняют роль трансмиттеров в передаче сигналов от половых гормонов (эстрогенов, андрогенов), а также осуществляют посреднические функции между лептином и ГнРГ-секретирующими центрами гипоталамуса, в результате осуществляя процессы «прямой/обратной связи» в пределах гонадной оси и сигнализируя об энергетическом балансе в названные центры [39].…”
Section: Peptic Ulcer Of the Stomach And Duodenum In Geriatrics -One ...unclassified
“…Репродуктивное старение, в частности старение яичников, у человека остается малоизученным. Многими исследователями показано, что репродуктивное старение характеризуется снижением экспрессии КП в гипоталамусе [27,30]. С другой стороны, женщины со сниженным овариальным резервом имеют значительное увеличение симпатических нервных волокон в яичниках, стимуляция которых β-адреномиметиками индуцирует экспрессию КП яичниками [31].…”
Section: роль кисспептинов в старении репродуктивной системыunclassified
“…In ageing rats, the number of KNDy neurons are reduced, resulting in a reduced level of pulsatile secretion of GnRH [ 64 ]. Both mRNA and protein levels of KPs and KPR are significantly decreased in the hypothalamus of ageing rats [ 112 ]. However, changes in the numbers of KP neurons and level of KP expression in humans differs from their rodent counterparts [ 113 ].…”
Section: Sexual Dimorphism In Hypothalamic Kisspeptin Expressionmentioning
confidence: 99%